User Experience Survey on Veterinary Clinic Online Pet Adoption System - Mirza Farzana Zainal; Nurul Aina Shamimi Mohd Shamsul Sharim; Siti Nurhaliza Ahmad Aznam; Rahmat, Hazwani (Multidisciplinary Applied Research and Innovation, 2025)
Stray animals are frequently found on the streets, and people will bring them to a veterinary clinic to get them treated. However, they will be returned to the wild as no one would adopt them. This is why a Veterinar Clinic Online Pet Adoption System has been created so the veterinary clinic, Mawrose Animal Clinic, Pagoh, can manage it. The system was developed using the Waterfall Methodology. This system has five functional modules, including registering and storing the pets’ information, appointment scheduling, filtering options, and a WhatsApp reminder for adopters to pick up their pets. The system is used for two types of users: the adopters and the veterinary clinic’s staff. The adopters can use this system to find a suitable pet and schedule an appointment to pick their new companion. The staff can register new pets into the system, manage the registered pets with their adoption status, and remind the adopters via WhatsApp. In conclusion, the Veterinar Clinic Online Pet Adoption System still needs to add more improvements, such as having a list for users to see which pet they have adopted and when their appointments would be held on before it is a proper solution for veterinary clinics to help stray animals to find a new home. Overall, the system is relatively acceptable to the survey participants as it has achieved most of their expectations.